Exploration of Learners' Creative Thinking in Applying the Concept of Division in Class VII Junior High School - Wilda Yanti; Sugiatno; Evi Noviani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This study aims to describe the creative thinking ability of seventh grade junior high school students in applying the concept of division and identify the factors that cause creative thinking difficulties in that context. This research is based on the importance of understanding mathematical concepts, where creative thinking becomes the foundation in helping students overcome difficulties in understanding the concept of division. The method used was qualitative with an explorative approach. Participants were selected using a purposive sampling technique, focusing on learners who were considered to be able to provide in-depth insights into their creative thinking abilities and the difficulties they faced. The results showed that learners were generally able to generate ideas quickly (fluency) and connect concepts with solutions in a relevant manner, although there were some ideas that were less relevant. Most learners also show flexibility by using various methods in solving problems, but there are some who tend to use only one method. In terms of originality, unique and structured ideas were found, although some were less structured or unable to develop ideas completely. In terms of elaboration, some learners were able to detail ideas well, while others showed weaknesses in detailing and developing ideas. Factors that cause creative thinking difficulties include lack of understanding of basic concepts, limitations in connecting prior knowledge, lack of practice and time, low level of confidence, lack of practice in working on open-ended problems, learning methods that do not support creativity, and lack of motivation.